Imagining a future without oil for car-dependent cities and regions - Newman, Peter (Island Press, 2013)
The period from the 1930s to 2008 was the era of cities based on the Internal Combustion Engine (ICE). The Global Financial Crash (GFC) of 2008 and the issues of peak oil and climate change seem to have ended the domination of this technology, though it will take some time for it to phase out. The limitations of ICE technology have exercised the minds of many technologists and regulators who have struggled to make cleaner and greener cities that have less smog. But the biggest force driving the need to phase out ICE-based mobility is the problem of oil. As oil production reaches its decline phase, the overwhelming need to find more oil has led to more and more dangerous deep-sea oil wells and options like burning rocks filled with tar sands or deep fracking of trapped oil.